(untitled) (The Peerian Journal, 2024)
Egg for intended Poultry in factories poultry for necessary has been microclimate parameters create for created don’t build with vermiculite nozzle part on the walls convection it ’s hot transmission and heat mass exchange processes analysis take on went studies as a result equipment laboratory conditions samples prepared and to practice current done Prepared don’t build the air channels dimensions 0.8...12mm in between experience works take went and most A convenient option is a 10 mm interval choose received Poultry buildings for microclimate provider nozzle part from vermiculite prepared from the equipment use as a result external access of air temperature decreased by 8-10 ℃and relative air humidity increased by 60-70%.